PEMBERDAYAAN KADER DENGAN “GERTING” GERAKAN ANTI STUNTING MELALUI EDUKASI DAN PENGOLAHAN PANGAN ORGANIK SEBAGAI UPAYA PENCEGAHAN STUNTING DI KECAMATAN TATAH MAKMUR - Dwi Rizki Febrianti; Yuliana Salman; Abdul Mahmud Yumassik (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Stunting is a condition of malnutrition that is related to past nutritional deficiencies. The cause of stunting is a multi-dimensional factor and is not only caused by a lack of nutritional intake in pregnant women or toddlers. The government at the national level has issued various policies and regulations which are expected to contribute to reducing the prevalence of stunting, including: National Long Term Development Plan on 2005–2025. Based on data in 2021 from the Indonesian Nutrition Status Survey, South Kalimantan was in the 6th highest position with a stunting prevalence of 30%, while for districts/cities in South Kalimantan the 4th highest stunting prevalence is Banjar Regency (40.2%), Tapin (33.5%), Barito Kuala (32.4%), and Balangan (32.3%) which then became priority areas for handling stunting cases in 2022. This activity aims to empower the community in the anti-stunting movement through education and training on local organic food processing to be one solution in preventing and handling stunting in Tatah Makmur District, South Kalimantan. The implementation method by education about stunting, training in local organic food processing (moringa nuggets) and providing packages of ingredients for making moringa nuggets and evaluating activities through pre and post test questionnaires. The results of the service activities showed that from 30 Posyandu cadres in 13 villages on Tatah Makmur District, there was an increase in knowledge about stunting increase 33% and an increase in knowledge about healthy food for toddlers is 20%. This activity also increases cadre motivation as evidenced by the cadre's enthusiasm for processing moringa nuggets at Posyandu as an additional menu for toddlers. It is hoped that similar activities can be carried out again with the different innovations in order to accelerate the reduction of stunting in South Kalimantan.